Physicochemical and Melissopalynological Study of Some Honey Samples from the Algerian East Region - Ketfi, L; Draiaia, R; Necib, A; Mohamadi, N (My University, 2023)
The quantitative and qualitative analysis of honey components is the object of this study. These analyses are considered a physicochemical and melissopalynological tool that allows the study of some characteristics of honey. The analysis of ten (10) samples of Algerian honey is carried out to determine the pH, water content, electrical conductivity, ash content, acidity, hydroxymethylfurfural content, proteins, and sugar content. According to the obtained results, the physico-chemical parameters of the studied honeys comply with the European and international standards. The pollen spectrum indicated the presence of 23 plant families, mainly Fabaceae, encompassing a total of 65 honey species visited by foragers. Of the 10 honeys sampled and analyzed, six were monofloral, with the remainder showing no apparent dominance of any honey type. The most frequent plant species were eucalyptus (Eucalyptus sp.), Italian sainfoin (Hedysarum coronarium), and chickweed (Lathyrus sp.). Furthermore, the results obtained indicate that all honey (monofloral and polyfloral) showed a high degree of variability in the number of pollen grains